Mothering through domestic violence - Radford, Lorraine (Jessica Kingsley Publishers, 2006)
Introduction -- Walking on eggshells : mothering through domestic violence -- Resisting mother blaming -- Domestic violence and the maltreatment of children -- Children living with domestic violence : impacts and resilience -- Reasserting power and control in child visitation and contact -- Mother blaming in the courts -- Improving safety for women and children -- From blaming mothers to providing positive support : the role of welfare agencies -- Conclusion: Linking the three planets